Effects of prednisone on eosinophilic bronchitis in asthma: a systematic review and meta-analysis, - Sakae,Thiago Mamôru (2014)
OBJECTIVE: To evaluate the effect size of oral corticosteroid treatment on eosinophilic bronchitis in asthma, through systematic review and meta-analysis. METHODS: We systematically reviewed articles in the Medline, Cochrane Controlled Trials Register, EMBASE, and LILACS databases. We selected studies meeting the following criteria: comparing at least two groups or time points (prednisone vs. control, prednisone vs. another drug, or pre- vs. post-treatment with prednisone); and evaluating parameters before and after prednisone use, including values for sputum eosinophils, sputum eosinophil cationic protein (ECP), and sputum IL-5-with or without values for post-bronchodilator FEV1-with corresponding 95% CIs or with sufficient data for calculation. The independent variables were the use, dose, and duration of prednisone treatment. The outcomes evaluated were sputum eosinophils, IL-5, and ECP, as well as post-bronchodilator FEV1. RESULTS: The pooled analysis of the pre- vs. post-treatment data revealed a significant mean reduction in sputum eosinophils (↓8.18%; 95% CI: 7.69-8.67; p < 0.001), sputum IL-5 (↓83.64 pg/mL; 95% CI: 52.45-114.83; p < 0.001), and sputum ECP (↓267.60 µg/L; 95% CI: 244.57-290.63; p < 0.0001), as well as a significant mean increase in post-bronchodilator FEV1 (↑8.09%; 95% CI: 5.35-10.83; p < 0.001). CONCLUSIONS: In patients with moderate-to-severe eosinophilic bronchitis, treatment with prednisone caused a significant reduction in sputum eosinophil counts, as well as in the sputum levels of IL-5 and ECP. This reduction in the inflammatory response was accompanied by a significant increase in post-bronchodilator FEV1.